Catalytic combustion kinetics of methyl butanoate over Pd/γ-Al2O3 catalysts: An experimental and theoretical study. (5th April 2023) - He, Chenliang; Shi, Ying; Feng, Beibei; Ruan, Shanshan; Qin, Chunlan; Xu, Kangwei; Zhang, Lidong
Highlights: Homogeneous and catalytic combustion of MB were compared through experiments. Pd/Al2 O3 reduced the formation of a large number of unsaturated products. The temperature of the same conversion decreased by more than 400 K over Pd/Al2 O3 . L-H and MvK model synergistically describe the reaction mechanism. The DFT calculation shows the two different initial reaction paths of Pd/Al2 O3 . Abstract: Catalytic combustion technology is a promising prospect for the removal of pollutants and improvement of combustion efficiency. In this study, methyl butanoate (MB), a typical biodiesel surrogate was chosen to obtain insight into the catalytic reaction mechanism of biodiesels over Pd/γ-Al2 O3 catalyst. By comparing the homogeneous and catalytic combustion experiment result, it is found that the reaction temperature of the same conversion in catalytic combustion is reduced by about 400 K. The formation of a large of methyl acrylate (MA) and the significant reduction of aldehyde products reflect the change of the catalytic combustion reaction path on the surface of Pd/γ-Al2 O3 . Density functional theory (DFT) calculation shows that two different initial reaction paths (Pd + MB and PdO + MB) have lower energy barriers for the generation of CH3 CH2 CHCOOCH3 (MB2J) radicals and the MB2J goes through subsequent decomposition to form MA, which is consistent with the experimental result.